Profiling the genes affected by pathogenic TDP‐43 in astrocytes. (9th February 2014) - Huang, Cao; Huang, Bo; Bi, Fangfang; Yan, Linda H.; Tong, Jianbin; Huang, Jufang; Xia, Xu‐Gang; Zhou, Hongxia
Abstract Mutation in TAR DNA binding protein 43 (TDP‐43) is a causative factor of amyotrophic lateral sclerosis and frontotemporal lobar degeneration. Neurodegeneration may not require the presence of pathogenic TDP‐43 in all types of relevant cells. Rather, expression of pathogenic TDP‐43 in neurons or astrocytes alone is sufficient to cause cell‐autonomous or non‐cell‐autonomous neuron death in transgenic rats. How pathogenic TDP‐43 in astrocytes causes non‐cell‐autonomous neuron death, however, is not clear. Here, we examined the effect of pathogenic TDP‐43 on gene expression in astrocytes. Microarray assay revealed that pathogenic TDP‐43 in astrocytes preferentially altered expression of the genes encoding secretory proteins. Whereas neurotrophic genes were down‐regulated, neurotoxic genes were up‐regulated. Representative genes Lcn2 and chitinase‐3‐like protein 1 were markedly up‐regulated in astrocytes from primary culture and intact transgenic rats. Furthermore, synthetic chitinase‐3‐like protein 1 induced neuron death in a dose‐dependent manner. Our results suggest that TDP‐43 pathogenesis is associated with the simultaneous induction of multiple neurotoxic genes in astrocytes, which may synergistically produce adverse effects on neuronal survival and contribute to non‐cell‐autonomous neuron death. <boxed-text content-type="graphic" id="jnc12660-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text> Restricted expression of pathogenic TDP‐43 in astrocytes causes non‐cell‐autonomous motor neuron death in transgenic rats. As revealed by microarray assay, pathogenic TDP‐43 in astrocytes preferentially altered expression of the genes encoding secretory proteins. Whereas neurotrophic genes were down‐regulated, neurotoxic genes were up‐regulated. Therefore, TDP‐43 pathogenesis is associated with simultaneous induction of neurotoxic genes and repression of neurotrophic genes in astrocytes.